Creation of Parcelas 5.0 using the 5S framework (social, sustainable, smart, sensing and safe) to improve traditional farming in Mexico - Arturo Molina; Alondra Michel Sánchez López; Emigdio Martínez Jiménez; Ana Lidia Barcenas Cortés; Pedro Ponce (International Journal of Sustainable Engineering)
This paper presents a comprehensive solution for Parcelas 5.0, designed to enhance sustainable agriculture in Mexico by utilising photovoltaic energy, rainwater capture, precision agriculture, and vertical farming using the 5S framework – Social, Sustainable, Sensing, Smart, and Safe and exponential technologies (nanotechnology, biotechnology, information technology, cogno technology). The proposed novel reference model, a Solar-Powered Vertical Farming Hub, is a modular and scalable system that integrates renewable energy and resource-efficient farming technologies to optimise productivity and environmental sustainability on small parcels of land, known as ‘parcelas’. Photovoltaic panels provide off-grid energy, powering LED grow lights, climate control, and IoT sensors, while rainwater capture systems support a closed-loop irrigation system for water efficiency. Precision agriculture technologies, including IoT-connected sensors and data analytics, enable real-time monitoring of crop health and environmental conditions, optimising resource use and reducing waste. Socially, this solution empowers local communities by providing access to training, creating jobs, and enhancing food security through localised food production. The system is inherently sustainable, utilising renewable resources and minimising chemical inputs, while smart technologies and sensing capabilities are enhanced. Three cases (Portable Micro-Greenhouse, Pilot Greenhouse and Parcelas 5.0) to grow Cherry Tomatoes are described to explain the technology development evolution towards Parcelas 5.0.